2012
DOI: 10.1111/j.1464-410x.2012.11338.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards bloodless cystectomy: a 10‐year experience of intra‐operative cell salvage during radical cystectomy

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Guidance from the UK National Institute for Health and Clinical Excellence (NICE) on the use of intraoperative cell savage (ICS) has been in place for over 3 years and recommends its routine usage in all patients undergoing radical pelvic urological surgery. The current series describes the contribution of ICS to contemporary blood conservation strategies and the goal of ‘bloodless’ cystectomy. OBJE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…185 More recent non-randomised studies in urological cancer surgery and metastatic spinal surgery have shown ICS to decrease the need for allogeneic RBC transfusion with no apparent risk of decreased long-term survival from an oncological perspective. [186][187][188] Contamination of the surgical field (e.g. bowel surgery, penetrating abdominal trauma or infected wounds) has typically been considered as a contraindication for ICS.…”
Section: Cell Salvage Recommendationsmentioning
confidence: 99%
“…185 More recent non-randomised studies in urological cancer surgery and metastatic spinal surgery have shown ICS to decrease the need for allogeneic RBC transfusion with no apparent risk of decreased long-term survival from an oncological perspective. [186][187][188] Contamination of the surgical field (e.g. bowel surgery, penetrating abdominal trauma or infected wounds) has typically been considered as a contraindication for ICS.…”
Section: Cell Salvage Recommendationsmentioning
confidence: 99%
“…24 Therefore, it is reasonable to decrease the number of intraoperative blood transfusions. Various strategies, such as a combining epidural with general anesthesia, 25 new technical apparatuses for hemostasis, 26,27 autotransfusion using intraoperative cell salvage, 28 and meticulous surgical performance may help reduce blood loss, the need for …”
Section: Discussionmentioning
confidence: 99%
“…This technique allows the patient's own blood, which is otherwise discarded, to be collected intraoperatively and then re‐infused as washed red blood cells. The aim is to reduce the need for allogenic blood transfusion and thereby reduce the associated risks as described in our earlier publication .…”
Section: Discussionmentioning
confidence: 99%